‘Me inda nampak’ – Pronoun Use in Malay-English Codemixed Social Media Texts - 'Aqilah Aziz (J-Lalite: Journal of English Studies, 2020)
This paper investigates the use of English the first-person singular object pronoun ‘me’ as a subject in conversation on WhatsApp and Telegram between university students in their twenties. It was found that the feature occurs more when interlocutors are code switching, especially in paired chats when ‘me’ often replaces the Malay pronoun aku or saya. This paper explores reasons for this, and how this feature has come to be used in synchronous electronically mediated conversations between young Bruneians. The findings show that using ‘me’ serves as a polite speech marker which is perceived as a softer expression than Malay aku in conversations, depending on the interlocutors.